Representations of Gender and Power on the “Time” Magazine Covers - Vitkūnė-Bajorinienė, Aistė; Šarkauskienė, Skirmantė (Information & Media, 2025)
Gender representations in the media and their relationship with signs of power remain a relevant topic in academic discourse. Power representations in the media play a significant role in shaping and reinforcing social norms, values, and attitudes, making the covers of prominent international magazines effective ideological tools. The study aimed to semantically analyze visual and textual signs of power on the covers of the Time magazine with the objective to reveal their connections with gender representations. Issues of the magazine from 2002, 2012, and 2022 were selected for analysis to identify ideological trends and potential changes in attitudes. A qualitative analysis of thematic, compositional, symbolic, and textual codes was conducted on the selected 122 covers featuring images of adults. It was found that the covers published in 2002 and 2012 are distinguished by dominant associations of masculinity and power. Meanwhile, representations of femininity and power on the covers of those years appear only in cases where women with significant symbolic capital are depicted. The covers of 2022 prominently stand out, due to proportionally presenting images of both women and men, as well as one transgender person. However, a deeper analysis of symbolic and compositional codes has revealed that the representation of power is still more closely associated with masculinity, while women’s photographs tend to highlight sexuality, weakness, and vulnerability. It becomes clear that although the portrayal of the relationship between power and gender in the Time magazine has changed over the past decades, the traditional patriarchal ideological tendencies remain.